XIII зууны Монгол ба Зүүн өмнөд Азийн орнуудын худалдаа соёлын харилцаа - С, Дашцэвэл (Journal of International Studies, 2009)
English title: Trade and cultural relations between Mongolia and South East Asia in the XIII century